MULTICULTURALISM AND RELIGIOUS-BASED CONFLICT: EVENTS OF CONFLICT BASED ON ETHNICITY, RELIGION, RACE, AND INTER-GROUP RELATIONS (SARA) IN THE CITY OF PONTIANAK - Lailial Muhtifah (Al-Albab, 2013)
There is a tendency of similar idea that caught the conflict prevention and management efforts nowadays to the articles of the Charter of Medina which was religious-based and containing the theory of civil society. It I mostly on the handling of conflict which tends to take preventive measures and to stop the conflict directly, as well as making a comprehensive synergistic effort to mange conflict. Conflict prevention is a core component of a comprehensive Conflict Management Program. This paper explores the conflict that occurred in Ponianak between a group of people from ethnic Dayak and members of an Islamic organization in 2012 which includes an important lesson for the people of West Kalimantan, both for the government and the community elements especially in dealing with a dispute between different groups of people. An integrative prevention has been proven to be able to answer the question of handling a conflict that has a potential to escalate into a full-scale riot. This work concludes that an integrative conflict handling model may become a viable alternative model to be adopted by the community of West Kalimantan in particular and other societies in general. A synergic integrative conflict handling model that reflects local wisdom of the people of Pontianak is expected to inspire real peace for various communities with a multicultural background. Key words: multicultural, religious-based conflict, ethnicity, religion